Collagenous Colitis and Spondylarthropathy - Kaouther Ben Abdelghani; Hana Sahli; Leila Souabni; Selma Chekili; Salwa Belhadj; Selma Kassab; Ahmed Laatar; Leith Zakraoui (Case Reports in Medicine)
Collagenous colitis is a recent cause of chronic diarrhea. Cooccurrence with spondylarthropathy is rare. We describe two cases: one man and one woman of 33 and 20 years old were suffering from spondylarthropathy. They then developed collagenous colitis, 4 and 14 years after the onset of spondylarthropathy. The diagnosis was based on histological features. A sicca syndrome and vitiligo were observed with the female case. The presence of colitis leads to therapeutic problems. This association suggests a systemic kind of rheumatic disease of collagenous colitis.